Consumer Bankruptcy, Bank Mergers, and Information - Allen, Jason; Damar, H. Evren; Martinez-Miera, David (Review of Finance, 2016)
Abstract This article analyzes the relationship between consumer bankruptcy patterns and the destruction of soft information caused by mergers. Using a major Canadian bank merger as a source of exogenous variation in local banking conditions, we show that local markets affected by the merger exhibit an increase in consumer bankruptcy rates post-merger. The evidence is consistent with the most plausible mechanism being the disruption of consumer–bank relationships. Markets affected by the merger show a decrease in the merging institutions’ branch presence and market share, including those stemming from higher switching rates. We rule out alternative mechanisms such as changes in quantity of credit, loan rates, or observable borrower characteristics.